2018
DOI: 10.3892/mmr.2018.8592
|View full text |Cite
|
Sign up to set email alerts
|

Interleukin‑10 promotes primary rat hepatic stellate cell senescence by upregulating the expression levels of p53 and p21

Abstract: Liver fibrosis is characterized by the excessive deposition of extracellular matrix (ECM) components, and activated hepatic stellate cells (HSCs) are a primary source of ECM. Several studies have revealed that the induction of HSC senescence may reduce liver fibrosis. The effect of interleukin-10 (IL-10) on the senescence of activated HSCs is not fully understood. Therefore, the present study examined its effects and potential mechanisms in activated primary rat HSCs. Collagenase perfusion and density gradient… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
21
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(22 citation statements)
references
References 25 publications
1
21
0
Order By: Relevance
“…IL-10 is involved in downregulating the pro-inflammatory processes in liver fibrosis [7]. In vivo studies showed that IL-10 inhibits the expression of aHSCs markers demonstrating its anti-fibrotic effects [97,98]. In a more recent study, IL-10 was shown to promote cellular death of aHSCs by senescence and upregulation of p53 and p21 expression [98].…”
Section: Anti-inflammatory Cytokinesmentioning
confidence: 99%
See 1 more Smart Citation
“…IL-10 is involved in downregulating the pro-inflammatory processes in liver fibrosis [7]. In vivo studies showed that IL-10 inhibits the expression of aHSCs markers demonstrating its anti-fibrotic effects [97,98]. In a more recent study, IL-10 was shown to promote cellular death of aHSCs by senescence and upregulation of p53 and p21 expression [98].…”
Section: Anti-inflammatory Cytokinesmentioning
confidence: 99%
“…In vivo studies showed that IL-10 inhibits the expression of aHSCs markers demonstrating its anti-fibrotic effects [97,98]. In a more recent study, IL-10 was shown to promote cellular death of aHSCs by senescence and upregulation of p53 and p21 expression [98]. Another anti-inflammatory cytokine is IL-22 that belongs to the IL-10 family and it is produced by innate immune system cells [99][100][101].…”
Section: Anti-inflammatory Cytokinesmentioning
confidence: 99%
“…Recently, we found that IL-10 promoted primary rat HSCs senescence by up-regulating the expression of p53 and p21 in vitro. 20 Moreover, we demonstrated that induction of HSCs senescence by IL-10 may be associated with p53-mediated signaling pathway in vitro . 21 As p53 plays a vital role in the senescence of activated HSCs mediated by IL-10 and then affect the progression of fibrosis, we sought to determine whether p53 knockdown could affect the senescence of activated HSCs and degradation of fibrosis mediated by IL-10.…”
Section: Introductionmentioning
confidence: 78%
“…Elimination of the injury stimulus causes aHSCs to undergo apoptosis (72), senescence (73), or reversal to quiescent or the so-called "inhibited phenotype" (iHSC) leading to regression of fibrosis (8,13,(74)(75)(76). IL10 and IL22 can be critically involved in the fibrosis reversal process as evidenced by IL10-induced inhibition of the expression of the activation markers in aHSCs (77)(78)(79), and IL10-and IL22-induced aHSC death by senescence (80,81). It is important to note that iHSCs can be rapidly reactivated upon return of the injury stimulus causing accelerated development of fibrosis (75).…”
Section: Activation Of Hscs and Liver Fibrosismentioning
confidence: 99%